Tracking Children Location Using LORA With Body Temperature Sensing Function - Narudin, Mohammad Nazrin; Mohd Ralim, Nadilah (Journal of Computing Technologies and Creative Content, 2020)
Nowdays, parent always busy with work at office, construction site and etc place. By having tracking children device, the parent can monitor their children situation. Beside that, by developed exisiting technology for children safety hopefully it can function well. Using lora device technology which is LoRa-02 Module (SX1278 433mhz) as main objective and additional function as detecting the temperature body children using MLX90614-Temperature Sensor module. More than that for tell the location of the children need GPS so by using GPS NEO Module as showing the children location. Last but not least this project using concept transmitter and receiver. The transmitter device will hold children while receiver device will hold by parent. The transmitter device will always transmit their data to the receiver device that hold by parent and parent can always get the data children by open the Blynk application.